The Influence of Service Quality Toward Customer Loyalty at Five-star Hotel in Bali - Clara K, Benedicta; Margaretha, Fransisca; Wirawan, Stevany Elizabeth; Wowor, Wulanmeiaya (IJOSMAS, 2022)
The growth of five-star hotels has increased and developed in the Province of Bali, which is the number one foreign exchange contributor from the tourism sector, therefore, leads to increasingly heavy competition in the service sector. This study aims to discover the influence of service quality on customer loyalty at five-star hotels in Bali Province. This study uses quantitative research methods with hypothesis testing. The demography refers to domestic tourists or Indonesian citizens who have stayed at five-star hotels in Bali Province. The data that collected from questionnaire using Likert scale. The number of samples taken was 161 respondents with a convenience sampling technique, non-probability sampling technique. Techniques for analyzing data are descriptive analysis, data quality testing, and hypothesis testing using validity, reliability, classic assumption, correlation coefficient analysis, determination coefficient analysis, and multiple regression analysis, and t-test. Based on the research results gained through SPSS, it shows that the value of Sig.0.000 < 0.05 and the t-count value is 6,862 > the t-table value is 1,975, be concluded that the Service Quality (X) variable influences the Customer Loyalty (Y) variable Keywords — service quality, customer loyalty, Bali, five-star hotel, SPSS, convenience sampling